Extraction of Caffeine from Spent Coffee Ground by Solid-liquid Extraction (Baghdad Science Journal, 2024)
The current research aims to utilize the spent coffee ground as a feedstock which is a waste material with a negative effect on the environment to extract natural bioactive valuable caffeine and determine the effective parameters of the extraction process efficiency in terms of caffeine concentration. The key studied parameters included extraction time 0- 150 min, temperature  25-55˚C, mixing speed (180-450 rpm), pH of suspension (4-9), and solvent type. The results of the experimental work showed that changing the pH of the suspension has a significant impact on the recovery rate of caffeine. When only water was used as a solvent, the concentration of caffeine increased from 135.061 (mg/L) to 2478.179 (mg/L) by increasing the pH of the suspension to 9. Another promising finding is that by changing the solvent type to an aqueous organic solvent, where the recovery of caffeine augmented remarkably. When 20% ethanol-water was utilized as a solvent and at the pH of 6 (the original pH) of the suspension, the concentration of obtained caffeine increased from 135  mg/L  to 213  mg/L. Furthermore, increasing the ethanol percentage to 80%, rising the caffeine concentration to 464  mg/L at the same pH. adjusting the pH of the suspension to 7, resulted in rising the obtained caffeine concentration to 2386.13 mg/l with a solvent concentration of 80% ethanol.